Calibration method for a structured light measurement system with two different focal length cameras. (September 2015) - Dong, Shengsheng; He, Bingwei; Lin, Chang; Zhao, Qiang; Shen, Henghua
Highlights: The method simplifies the extrinsic calibration of the high-resolution system. Two structured light systems with different resolutions are merged into one. A novel reconstruction strategy based on the two-resolution system is proposed. The system fast reconstruct the object and also obtain the details of the features. The novel reconstruction strategy significantly economizes the storage resources. Abstract: During reconstructing objects with complex shapes, 3D object surfaces are anticipated with an elaborate description to surface features and a fast acquiring speed. While a Camera–Projector Structured Light (CPSL) system with a constant focal length cannot achieve the two goals. The CPSL system with a Long Focal Length (LFL) camera has a high resolution and a small measurement area, therefore, high sampling density and low measurement efficiency. Conversely, the system with a Short Focal Length (SFL) camera has high measuring efficiency without enough sampling density. To accomplish the two goals, we propose a novel system integrating with two types of CPSL system. One system with the SFL camera fast obtains the overall morphology of objects. Another with the LFL camera acquires the details of surface features very well. To integrate them, a novel calibration method is presented. Experimental results verify the robustness and accuracy of the proposed calibration method.